Heavy metal contamination in vegetables grown around peri-urban and urban-industrial clusters in Ghaziabad, India. Issue 3 (2nd April 2016) - Chabukdhara, Mayuri; Munjal, Amit; Nema, Arvind K.; Gupta, Sanjay K.; Kaushal, Rajendra Kumar
ABSTRACT: Heavy metal contamination of agricultural soils resulting from rapid industrialization and urbanization is of great concern because of potential health risk due to dietary intake of contaminated vegetables. The present study aims to evaluate the status of heavy metals contamination of agricultural soils and food crops around an urban-industrial region in India. Transfer factor values of Cu, Cr, Pb, Cd, Zn, and Ni from soil to vegetable was estimated. The mean heavy metal concentrations (mg/kg) in agricultural soils (Cu: 17.8, Cr: 27.3, Pb: 29.8, Cd: 0.43, Zn: 87, Mn: 306.6, Fe: 16984, and Ni: 53.8) were within allowable concentrations for Indian agricultural soil. The concentrations of Pb, Cd, Zn, and Ni in crops/vegetables exceeded the World Health Organization/Food and Agriculture Organization safe limits. Relative orders of transfer of metals from soil to edible parts of the crops/vegetables were Cd > Pb > Ni > Zn > Cu > Cr. The enrichment factors of heavy metals in soil indicated minor to moderately severe enrichment for Pb, Cd, and Ni; minor to moderate enrichment for Zn; no enrichment to minor enrichment for Mn; and no enrichment to moderate enrichment for Cu at different sites. Ecological risk index of soil showed considerable contamination in one of the wastewater irrigated sites.